Pengaruh Gaya Kepemimpinan, Budaya Organisasi Dan Hubungan Interpersonal Terhadap Kinerja Pegawai - Dhimas Al Annas; Andhyka Tyaz Nugraha; Muhammad Miftahul Abid (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to examine the influence of leadership style, organizational culture, and interpersonal relationships on employee performance at the Department of Public Works for Human Settlements, Spatial Planning, and Irrigation in Musi Rawas Regency. Furthermore, this research investigates the mediating role of organizational culture in the relationship between leadership style and interpersonal relationships with employee performance. The research applies a Mixed Method Research (MMR) approach, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS version 3. A total of 62 employees participated by completing a structured questionnaire. The findings reveal that both leadership style and interpersonal relationships have a positive and significant impact on organizational culture and employee performance. However, organizational culture does not significantly affect performance, nor does it mediate the relationship between the independent variables and performance. These results provide valuable practical implications for institutions seeking to improve employee performance by strengthening leadership practices and fostering positive workplace relationships.